Bioinspired Mechanically Robust Metal‐Based Water Repellent Surface Enabled by Scalable Construction of a Flexible Coral‐Reef‐Like Architecture. Issue 39 (7th August 2019) - Luo, Xiao‐Tao; Li, Chang‐Jiu
Abstract: Mechanical robustness is a central concern for moving artificial superhydrophobic surfaces to application practices. It is believed that bulk hydrophilic materials cannot be use to construct micro/nanoarchitectures for superhydrophobicity since abrasion‐induced exposure of hydrophilic surfaces leads to remarkable degradation of water repellency. To address this challenge, the robust mechanical durability of a superhydrophobic surface with metal (hydrophilic) textures, through scalable construction of a flexible coral‐reef‐like hierarchical architecture on various substrates including metals, glasses, and ceramics, is demonstrated. Discontinuous coral‐reef‐like Cu architecture is built by solid‐state spraying commercial electrolytic Cu particles (15–65 µm) at supersonic particle velocities. Subsequent flame oxidation is applied to introduce a porous hard surface oxide layer. Owing to the unique combination of the flexible coral‐reef‐like architecture and self‐similar manner of the fluorinated hard oxide surface layer, the coating surface retains its water repellency with an extremely low roll‐off angle (<2°) after cyclic sand‐paper abrasion, mechanical bending, sand‐grit erosion, knife‐scratching, and heavy loading of simulated acid rain droplets. Strong adhesion to glass, ceramics, and metals up to 34 MPa can be achieved without using adhesive. The results show that the present superhydrophobic coating can have wide outdoor applications for self‐cleaning and corrosion protection of metal parts. Abstract : Poor mechanical durability is the biggest challenge for practical applications of superhydrophobic surfaces. To address this, a metallic flexible coral‐reef‐like hierarchical architecture is scalably constructed. Although the architecture is intrinsically hydrophilic, the fluorinated architecture retains excellent water repellency after cyclic sand‐paper abrasion, bending, sand‐grit erosion, and knife‐scratching. This work provides a new strategy to achieve excellent mechanically robust superhydrophobic surfaces.